Is AI better than humans? unveiling the boundary conditions under which virtual influencers outperform human influencers in endorsing sustainable products - Yan, Xu; Huam, Hon Tat; Sade, Abu Bakar (Multidisciplinary Digital Publishing Institute, 2024)
With the rising trend toward sustainable consumption and the pivotal role of social media in the buying behavior, brands are keen to promote sustainable products through these platforms. Virtual influencers (VIs) have emerged as lower-cost and scandal-resistant alternatives to human influencers (HIs). However, their artificial nature may evoke credibility concerns, potentially undermining marketing effectiveness. Currently, it is unclear whether humans or virtual influencers achieve better endorsement outcomes for sustainable products. This study explores the effectiveness of VIs and HIs in endorsing sustainable products and the conditions under which VIs may outperform HIs. Through two studies (N = 1097), we investigate the impact of influencer type, advertising appeals, and product involvement on consumer purchase intentions and brand attitudes. Our findings reveal that, in low-involvement product scenarios with emotional appeals, HIs are more effective, while in high-involvement product scenarios featuring rational appeals, VIs exhibit superior effectiveness. These results suggest that the choice of influencer type should be tailored to the product involvement level and the nature of the advertising appeal, providing guidance for brands to enhance the impact of their green marketing strategies.